Studi Numerik Pengaruh Jarak Silinder Pengganggu terhadap Returning Blade pada Performa Turbin Angin Savonius Fin - Mokhamad Prayitno; Priyo Agus Setiawan; Nopem Ariwiyono (Politeknik Perkapalan Negeri Surabaya, 2023)
The performance of Savonius wind turbine has increased in the previous experimentalstudies with 1 additional fin and various disturbing cylinder distance in front of returning blade.Although the performance has increased, validation is needed through experiments . Therefore, furtherresearch is needed. The research uses Computational Fluid Dynamic (CFD) with 3-dimensional modelto obtain an increase on the turbine performance. In this simulation the solver chosen is pressure based with transient time mode. In the Savonius wind turbine simulation, the model used is the realizable k-epsilon model. Numerical method can validate experimental study. The turbine uses 1 additional fin with 40 cm in diameter and height. The variation of disturbing cylinder distance is S/d = 1.4 ; S/d =1.7; s/d = 2.0; s/d = 2.3 with wind speed of 5 m/s. Simulations are also carried out to determine thevalue of Coefficient of Power (Cp). The final result is there is 5,40% increase on the turbineperformance at the distance S/d = 1,7 , 5 m/s speed, and 1,0 TSR. The Coefficient of Power (Cp)simulation value is 0,389.